A Resolução de Problemas como Metodologia para o Ensino da Matemática: Uma Abordagem sobre Divisibilidade e Congruência - Caetano Júnior, Gilberto (2021)
The teaching of Mathematics, even today, is one of the great challenges of Education. Its teaching, for many years, prioritized the abstract character and the practical part was left in the background. Because of that, a great part of the students started seeing Mathematics as a disconnected science from reality and with no practical use. Fortunately, in recent years, discussions about this topic and the search for new teaching methodologies have rescued students’ interest in studying and learning Mathematics. From this perspective, Problem Solving as a methodology for teaching Mathematics has proven to be an extremely effective tool and it can be used for teaching practically all mathematical content. Specifically, in this paper, the objective is to work the ideas about Divisibility and Modular Congruence using Problem Solving as a methodology for the introduction of the referred contentes The paper was divided into three parts, the first one is the research of the theoretical framework, the second one a field approach, in which students from the 8th and 9th grade of Elementary School of a Public School took part, and the third part, the analysis and discussion of results. For the second part of the work, a list of issues with mathematical problems involving Divisibility and Congruence was applied and the students had a predetermined time to solve it. After analyzing and tabulating the results, the list was commented and solved together with the students, who had the opportunity of getting in touch with the contents that were unknown to them, in a different way. The analysis of the results revealed the importance of using Problem Solving as a teaching tool, motivating students’ learning and making them protagonists in the construction of their own knowledge.